Integrasi Filsafat Dan Agama Dalam Perspektif Ibnu Rusyd - Ngazizah, Dhaoul; Mawardi, Kholid (Jurnal Ilmiah Mandala Education (JIME), 2022)
This article was written with the aim of discussing the integration between religion and philosophy in the view of Ibn Rusyd. In classical civilization there have been long debates and struggles caused by differences of opinion between philosophers and jurists. One side of the philosophers based their ideas on the thinking of the intellect, while the other side argued based on revelation. Ibn Rusyd, a Muslim philosopher who was very fond of science, sought to integrate philosophy and religion. Ibn Rusyd said that Philosophy and Religion are interrelated and have the same goal, which is to seek the truth. Philosophy is the product of the mind of man and Religion is based on the revelation of God. Epistemologically, the method taken by Ibn Rusyd in order to unite religion with philosophy, by way of Ta'wil and Qiyas. This is also what he has poured in a book entitled fashl al-maqal wa taqrir ma bain al hikmah wa al-syariah min al-ittishal.